Comparative Analysis of West African School Certificate Examinations and National Examination Council Results in Mathematics, English Language and Biology from 2001 – 2006 in Oyo State, Nigeria (2009)
The study investigated the relationship between the grades awarded by both WAEC and NECO in Mathematics, English language and Biology papers in SSCE from 2001 - 2006 in Oyo State. The sample consists of 1468 participants. Pearson product moment correlation test statistic was used for analyzing the data generated in the study. The finding reveals that, there is significant correlation between the grades awarded by both WAEC and NECO from 2001 - 2006 in Mathematics, English Language and Biology papers which are principal subjects at ordinary level examinations. The necessary recommendations were made fee students, parents, guidance counsellor, government and stake holders on the reliability and validity of SSCE conducted by both WAEC and NECO.